Novel crosslinkable epoxy resins containing phenylacetylene and azobenzene groups: From thermal crosslinking to flame retardance. (December 2015) - Liu, Bo-Wen; Zhao, Hai-Bo; Tan, Yi; Chen, Li; Wang, Yu-Zhong
Abstract: Several kinds of novel flame-retardant-free and thermo-crosslinkable epoxy resins (EPs) containing azobenzene or/and phenylacetylene groups have been synthesized and characterized, and the flame retardant properties as a result of thermal crosslinking during combustion were investigated in detail. Crosslinking behaviors were tested by simultaneous thermogravimetry–differential scanning calorimetry (TGA–DSC). Thermal stabilities were investigated by thermogravimetric analysis (TGA). Flame retardance of the resulting EPs was evaluated through LOI tests, and combustion behaviors were studied via cone calorimetry and micro-combustion calorimetry (MCC), which further confirmed that flame retardance of these EPs was significantly improved, despite the absence of conventional flame retardant. Py–GC/MS analysis was used to investigate the degradation mechanism of these epoxy resins, and the results confirmed that the flame-retardant activity of epoxy resins mainly took effect in the condensed phase. The chemical constitution of the char layers were investigated by XPS and Raman spectrum. The co-crosslinking behavior between azobenzene and phenylacetylene groups was predicted and confirmed, which led to the most compact char layer, therefore resulted in the best flame retardance of these EPs.